PW 1067 Improving recovery outcomes in burns survivors: a systems approach. (November 2018) - Jagnoor, Jagnoor; Chamania, Shobha; Bekker, Sheree; Potokar, Tom; Ivers, Rebecca
Abstract : Background: Burns have been described by the World Health Organisation as the 'forgotten global public health crisis'. India has one of the largest burden of burn-related morbidity and mortality globally, but little is known about burn care and rehabilitation practices. Non-fatal burn injuries contribute to substantial morbidity and disability and can have long-term economic and psycho-social impacts on burn survivors and their families, much of which could be prevented with adequate management, and access to quality care and rehabilitation. The aim of this study was to identify priority policy issues and understand health system challenges associated with recovery outcomes for burns survivors in India. Methods: A qualitative study using focus groups (n=1) and in-depth interviews (n=19) was conducted with burn survivors and their carers, health service providers, and key informants. Results: Multiple referrals, gaps in access to care, transport and financial barriers were key challenges for burn survivors to receiving adequate care. Health professionals identified inadequate skills and lack of motivation as major concerns for delivering care. Shortages in human resources, equipment, infrastructure and supplies, and the absence of evidence based guidelines on burns-rehabilitation compromised outcomes. Poor communication on the need for rehabilitation was raised by health providers and patients with little understanding of recovery potential and fatalistic attitudes prevailing. Stigma associated with burn injuries was a challenge within the healthcare system, and at the community level. Conclusion: The absence of coordinated efforts within the health care system to manage and treat burn injuries has led to very poor outcomes and quality of life for burn survivors. Community-based rehabilitation programmes are potential solutions to overcome these challenges. The recent inception of the National Program for Prevention and Management of Burns Injuries in India provides an opportunity to test and develop solutions using a health systems approach for improving recovery outcomes.